The Influence of Leadership Styles and Incentive on Employee’s Work Satisfaction in the Production Department of PT Toarco Jaya Tora - Maya Maya; Grace Jenny Soputan; Roddy A. Runtuwarouw (AIBPM Publisher, 2020)
This study aims to determine the effect of leadership style and incentives on employee’s job satisfaction in PT Toarco Jaya Toraja's production department. This study made use of survey, while the data were collected by questionnaires to capture the leadership styles, incentives, and job satisfaction, as well as interviews to fulfill the data on incentives. The questionnaires were distributed to 33 employees of the production department. The data were processed and analyzed using multiple linear regression analysis. The analysis resulted an equation Y = 4.963 + 0.490X1 + 0.620X2 + e. The correlation coefficient (R) is 0,900. Adjusted R square or R2 was 0.810. The F test shows that the Fvalue ≥ Ftable (63,762≥3.32) or sig 0.000 ≤ 0.05. Hypothesis testing indicates that the leadership style and incentives have a positive and significant effect on employee’s job satisfaction. Partially, job satisfaction is influenced by the leadership style, and employee’s job satisfaction is influenced by incentives.